Search for first generation scalar leptoquark pairs in pp̄ collisions at √s = 1.8 TeV - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; Astur, R; et al. (1998)
We have searched for first generation scalar leptoquark (LQ) pairs in the ev + jets channel using pp̄ collider data (∫ L dt ≈ 115 pb-1) collected by the DO experiment at the Fermilab Tevatron during 1992-1996. The analysis yields no candidate events. We combine the results with those from the ee + jets and vv + jets channels to obtain 95% confidence level (C.L.) upper limits on the LQ pair production cross section as a function of mass and of β, the branching fraction to a charged lepton. Comparing with the next-to-leading order theory, we set 95% C.L. lower limits on the LQ mass of 225, 204, and 79 GeV/c2 for β= 1, 1/2, and 0, respectively.